Fusarium Tropical Race 4 in Latin America and the Caribbean: status and global research advances towards disease management - Munhoz, Thayne; Vargas, Jorge; Teixeira, Luiz; Staver, Charles; Dita, Miguel (Frontiers in Plant Science, 2024)
Fusarium wilt of banana (FWB), caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense (Foc), poses an undeniable threat to global banana production. This disease has intensified in recent years, with the tropical race 4 (TR4) strain spreading rapidly. Since 2018, the number of affected countries has increased from 16 to 23, presenting a significant challenge to researchers, producers, and National Plant Protection Organizations (NPPOs) worldwide. The potential impact of TR4 in Latin America and the Caribbean (LAC) is particularly concerning. This region boasts seven of the top ten banana-exporting countries, and bananas and plantains are crucial for food security and income generation. In Colombia, where TR4 was detected in 2019, the disease has already spread from La Guajira to Magdalena, and it is currently affecting 20 large commercial export farms. In Peru, the disease was detected in 2021 and although still restricted to the northern region, flood irrigation and heavy rains associated with the Yaku cyclone, boosted pathogen spread, and more than 400 small organic banana farmers are currently affected. In Venezuela, TR4 detection occurred in 2023, with plantations across three states and five municipalities now affected. Worryingly, TR4 has also been confirmed in plantains, a staple food in the region. Current national responses in LAC primarily rely on preventive and reactive measures: preventing initial incursions and containing outbreaks to avoid further spread. However, the disease's relentless progression suggests that its eventual presence in all bananaproducing areas is likely. Therefore, exploring alternative management approaches beyond pathogen exclusion becomes crucial, both in affected and disease-free regions. This paper examines the current spread of TR4, focusing on epidemiological aspects and recent researchbased management options. Key epidemiological features were highlighted, drawing practical examples from various scales (plots to landscapes) and utilizing experiences from LAC's fight against TR4. The paper also reviews field-tested approaches in biosecurity, biological control, resistant varieties, soil health, and integrated disease management, acknowledging the specific challenges faced by smallholder settings. In each section research initiatives were analyzed, identifying gaps, and proposing directions to minimize TR4 impact and accelerate the development of sustainable solutions for managing this devastating disease.